Weibull Reliability Method for Several Fields Based Only on the Modeled Quadratic Form - Piña Monarrez, Manuel Román (Taylor & Francis, 2021)
In this chapter, a practical and dynamic method to determine the reliability of a process (or product) is presented. The novelty of the proposed method is that it let us to use the Weibull distribution to determine the reliability index, by using only the quadratic form of the analyzed process (or product) as an input. So, since this polynomial can be fitted by using, e.g., simulation, mathematical and/or physical modeling, empirical experimentation and/or any optimization algorithm, the proposed method can easily be implemented in several fields of the smart manufacturing environment. For example, in the industry 4.0 framework, the proposed method can be used to determine, in dynamic form, the reliability of the analyzed product, and to give instantaneous feedback to the process. Therefore, to show the efficiency of the proposed method to determine the reliability in several fields, it is applied to the design, the quality and the monitoring product phases as well as to the fatigue (wearout and aging) phase. In order to let readers adapt the given theory to their fields and/or research projects, a detailed step by step method to determine the Weibull parameters directly from the addressed quadratic form is given for each one of the presented fields.